How Does A Father Construe Nrimo Ing Pandum Makaryo Kan Nyoto Philosophy In Early-Childhood? An Interpretative Phenomenological Analysis - Febritesna Nuraini; Djoko Purnomo; Abdul Latif; M Ishaq; Wahyu Widiastuti; Iyan Sofyan (Universitas Muhammadiyah Ponorogo, 2021)
One of the values maintained and internalized by the Javanese family is the valueof nrimo ing pandum, makaryo kang nyoto. A growing body of literature exploresthe fading Javanese values. However, studies on fathers’ experience during the value internalization process are still scarce. This study sought to understand how fathers see the Javanese philosophy of nrimo ing pandum makaryo kang nyoto. The participants of the study were three fathers in the Bantul region. The data of the study were collected using a semi-structured interview. The interview transcript was qualitatively analyzed using an interpretative phenomenological approach. Three superordinate themes were obtained, namely peace, disappointment when children give up easily, and efforts to introduce. Thefindings indicate the need for seeking effective efforts to help fathers maintain the Javanese philosophical value and see the effect on the children when it is properly internalized.